Pengembangan Marketplace Preng sebagai Platform Digital Penjualan Produk UMKM di Desa Karangmelok Kecamatan Tamanan Kabupaten Bondowoso - Januar Adi Putra; Fahrobby Adnan; Panca Oktawirani; Yeni Puspita (Forum Kerjasama Pendidikan Tinggi, 2022)
Karangmelok Village, Tamanan District, Bondowoso Regency has many excellent bamboo handicraft products that can be developed to boost the economy of its inhabitants, but this is not being utilized properly. The lack of utilization of technological developments is one of the main causes of the lack of recognition of the potential products of Karangmelok Village, Tamanan District, Bondowoso Regency. With the less effective use of technology, marketing is not optimal and results in small income received. The Community Service Team has conducted an analysis of the partner situation where it was found that the main problems mentioned occurred in the majority of MSMEs in Karangmelok Village, Tamanan District. Based on the problems above, it is proposed that community service activities utilize technology that can accommodate all Karangmelok Village SMEs, so that they can realize the village's dream of becoming an INDEPENDENT CREATIVE VILLAGE, besides that Karangmelok Village SMEs are also expected to increase competitiveness to realize UMKM Go Online which was initiated by the Ministry of Cooperatives and SMEs and the Ministry of Communication and Information of the Republic of Indonesia. The solution that will be offered is the development of a Marketplace system under the name Preng as a Digital Platform for Sales and Forecasting of MSMEs Product Trends in Karangmelok Village, Tamanan District, Bondowoso Regency to Realize MSMEs Go Online.